Cross-cultural trust - TAN, Hwee Hoon (Institutional Knowledge at Singapore Management University, 2017)
How and why do people trust each other? Does trust develop differently across cultures? Why is it important for organisations to develop a culture of trust? Professor Tan Hwee Hoon shares insights from her research in cross-cultural trust.